2019
DOI: 10.1016/j.cardfail.2019.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic Polymorphisms and Survival in African Americans With Heart Failure: Results From A-HeFT

Abstract: Background: Polymorphisms in adrenergic signaling affect the molecular function of adrenergic receptors and related proteins. The β1 adrenergic receptor (ADRB1) Arg389Gly, G-protein receptor kinase type 5 (GRK5) Gln41Leu, G-protein β-3 subunit (GNB3) 825 C/T, and α2c deletion affect adrenergic tone, impact heart failure outcomes and differ in prevalence by ethnicity. Their combined effect within black cohorts remains unknown. Methods and Results:We analyzed subjects from the African American Heart Failure Tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Indeed, as demonstrated by Ligget et al [ 104 ], while Leu41 carriers survived better than those presenting Gln41 variants, they exhibited a reduced response to β-blockers such as atenolol [ 107 ]. Conversely, another study among African Americans by Johnson et al [ 108 ] demonstrated that Leu41 negatively impacted on the survival of HF patients, but these effects seemed to be stabilized upon β-blocker usage. Together, these studies suggest the importance of patients’ genetic background and ethnicity, and how this drives the proper response to β-blocker therapy.…”
Section: Targeting β-Ar Signaling In Cardiovascular Disease: Grks Inh...mentioning
confidence: 99%
“…Indeed, as demonstrated by Ligget et al [ 104 ], while Leu41 carriers survived better than those presenting Gln41 variants, they exhibited a reduced response to β-blockers such as atenolol [ 107 ]. Conversely, another study among African Americans by Johnson et al [ 108 ] demonstrated that Leu41 negatively impacted on the survival of HF patients, but these effects seemed to be stabilized upon β-blocker usage. Together, these studies suggest the importance of patients’ genetic background and ethnicity, and how this drives the proper response to β-blocker therapy.…”
Section: Targeting β-Ar Signaling In Cardiovascular Disease: Grks Inh...mentioning
confidence: 99%
“…In these patients, we found 50% less cGMP in the carriers of the T117S variant than the noncarriers (WT CYB5R3 form) ( Figure 8H ). We next extended these studies with a meta-analysis to determine the association of CYB5R3 T117S with event-free survival in self-identified Black individuals from the Genetic Risk Assessment of Heart Failure (GRAHF) study in African Americans, a genetic substudy of the African American Heart Failure Trial (AHeFT) (ClinicalTrials.gov NCT00047775) ( 41 , 42 ), and the Genetic Risk Assessment of Cardiac Events (GRACE) study, a single-center genetic outcomes registry from the University of Pittsburgh Medical Center ( 43 , 44 ). For the combined outcome analysis, subjects receiving fixed dose combination therapy of isosorbide dinitrate and hydralazine (FDC I/H) were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…For analysis of the impact of the T117S genotype on clinical outcomes in chronic HFrEF, participants from 2 prospective genetic outcomes studies were combined. The GRAHF cohort was a genetic substudy of the AHeFT trial (ClinicalTrials.gov NCT00047775) ( 41 , 42 ). AHeFT was a placebo-controlled randomized trial of FDC I/H specifically in self-identified African Americans with chronic HFrEF.…”
Section: Methodsmentioning
confidence: 99%
“…Variability in response to BBs among HF patients may, in part, be explained by interindividual genetic variability ( 8 , 9 ). Examples of such variations are the single nucleotide polymorphisms (SNPs) in beta-adrenergic signaling genes, such as ADRB1 and ADRB2 , which encode for the β 1 - adrenergic receptor (AR) and β 2 – AR, respectively.…”
Section: Introductionmentioning
confidence: 99%